Pengabdian Mahasiswa untuk Meningkatkan Kesadaran Berperilaku Hidup Bersih dan Sehat pada Masyarakat Kampung Gunung Kapur dimasa Pandemi Covid-19 - Pradana, Hilman Nurhakim; Utami, Esty Puri (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
Clean and healthy living behavior is essential to apply in the time-sensitive covid-19. This was intended for any society to adapt and to increase everyone's immune system. Based on this awareness, we a part of KKN-DR sisdamas are trying to help people with the Kampung Gunung Kapur government personel. Through socializing of clean and healthy living behaviors, a video production played by the Kampung Gunung Kapur kids. We were able to raise public awareness of clean and healthy life behavior. We have also been able to raise awareness of people to keep the neighborhood clean in Kampung Gunung Kapur.